# How to Prove It - Solutions

## Chapter - 3, Proofs

### Summary

• To prove a goal of the form $\forall x P(x)$:
• Let $x$ stand for an arbitrary object and prove $P(x)$. If x is already being used in the proof for something, then choose an unused variable, say $y$, for the arbitrary object, and prove $P(y)$.
• Scratch work will look as:
Given:
Goal: $\forall x P(x)$
It will be transformed to:
Given:
Goal: $P(x)$
• Formal proof will look as:
Let x be arbitrary.
[Proof of $P(x)$ goes here.]
Since $x$ was arbitrary, we can conclude that $\forall x P (x)$.
• To prove a goal of the form $\exists x P(x)$:
• Try to find a value of $x$ for which $P(x)$ will be true. Then start the proof with “Let x = (the value decided)” and proceed to prove $P(x)$ for this value of $x$.
• Scratch work will look as:
Given:
Goal: $\exists x P(x)$
It will be transformed to:
Given:
Goal: $P(x)$
x = (the value decided)
• Formal proof will look as:
Let x = (the value decided).
[Proof of $P(x)$ goes here.]
Thus $\exists x P (x)$.
• To use a given of the form $\exists x P(x)$:
• Introduce a new variable, say $x_0$, into the proof for which $P(x_0)$ is true. Thus it can be assumed that P(x_0) is true. This rule of inference is called existential instantiation.
• Using a given of the form $\exists x P(x)$ is very different from proving a goal of the form $\exists x P(x)$, because when using a given of the form $\exists x P(x)$, there is no choosing for the value of $x$.
• To use a given of the form $\forall x P(x)$:
• Plug in any value, say a, for x and use this given to conclude that P(a) is true. This rule is called universal instantiation.
• It will be useful for cases when particular value, say $a$, of $x$ is already known or considered and thus it can be assumed that $P(a)$ is true.

Soln1

Suppose $\exists x(P(x) \to Q(x))$ is true at $x = x_0$. Thus we have $P(x_0) \to Q(x_0)$. Suppose $\forall x P(x)$. Then $P(x_0)$ is true. Since $P(x_0) \to Q(x_0)$ and $P(x_0)$ then $Q(x_0)$ is true. Thus $\exists x Q(x)$ is true. If follows that $\forall x P(x) \to \exists Q(x)$ is true.

Soln2

Suppose $x$ is arbitrary and $x \in A \cap B$, then $x \in A$ and $x \in B$. Suppose $x \notin C$. Since $x \in B$ and $x \notin C$, it follows that $x \in B \setminus C$. Now since $x \in A$ and $x \in B \setminus C$, it follows that $x \in (A \cap (B \setminus C))$. But $A \cap (B \setminus C) = \phi$. Thus the assumption $x \notin C$ is not correct. It follows that if $x \in A \cap B$, then $x \in C$. As $x$ is arbitrary, we have $A \cap B \subseteq C$.

Soln3

Suppose $x \in A$ and $x \in C$. Since $A \subseteq (B \setminus C)$, it follows $x \in B \setminus C$. Thus $x \in B$ and $x \notin C$. This contradicts the assumptions that $x \in A cap C$. As $x$ is artibrary, $A \cap C = \phi$.

Soln4

Suppose $x \in \mathcal P(A)$. Then $x \subseteq A$. Since it is given that $A \subseteq \mathcal P(A)$, it follows that $x \subseteq \mathcal P(A)$. Thus if $x \in \mathcal P(A)$ then $x \in \mathcal P ( \mathcal P(A))$. As $x$ is arbitrary, we get $\mathcal P(A) \subseteq \mathcal P( \mathcal P(A) )$.

Soln5

(a) Empty set: $\phi$.

(b) No. there is no other such set.

Soln6

(a)

Suppose $y = \frac {2x + 1} {x - 1}$. Putting the value of $y$ in $\frac {y+1}{y-2}$. We get:

Thus $\exists y (\frac {y+1}{y-2} = x)$

(b)

Given that $\frac {y+1}{y-2} = x$. Solving this for $y$, we get $y = \frac {2x + 1} {x - 1}$. Since $y$ is a real number, then $\frac {2x + 1} {x - 1}$ is real. Thus $x \neq 1$.

Soln7

Suppose $x > 2$ and $y = \frac {x + \sqrt {x^2 - 4}} {2}$. Putting this value of $y$ in $y + \frac 1 y$, we get:

$\quad = \frac {x + \sqrt {x^2 - 4}} {2} + \frac {2} {x + \sqrt {x^2 - 4}}$
$\quad = \frac { {(x + \sqrt{x^2-4})}^2 + 4} {2(x + \sqrt {x^2 - 4})}$
$\quad = x$

Thus $y + \frac 1 y = x$.

Soln8

Suppose $x \in A$. Since $A \in \mathcal F$, then $x$ must belongs to $\cup \mathcal F$. Thus we have $x \in A \to x \in \cup \mathcal F$. Since $x$ is arbitrary, we have $A \subseteq \cup \mathcal F$.

Soln9

Suppose $x \in \cap \mathcal F$. Since $x \in \cap \mathcal F$, then $x$ must belongs to all the set of $\mathcal F$. Now since $A \in \mathcal F$, it follows that $x \in A$. Thus we have $x \in \cap \mathcal F \to x \in A$. Since $x$ is arbitrary, we have $\cap \mathcal F \subseteq A$.

Soln10

Suppose $x \in B$. Since $\forall A \in \mathcal F(B \subseteq A)$, it follows that $\forall A \in \mathcal F(x \in A)$. Thus $x$ belongs to all the sets of $\mathcal F$. Or we can say that $x \in \cap \mathcal F$. It follows that $x \in B \to x \in \cap \mathcal F$. Now since $x$ is arbitrary, $B \subseteq \cap \mathcal F$.

Soln11

Suppose that $x \in \cap \mathcal F$. Thus $x$ belongs to all the sets of $\mathcal F$. Since $\phi \in \mathcal F$, then $x \in \phi$. But there is no such element that $x \in \phi$. Thus such $x$ does not exist. Or $\cap \mathcal F = \phi$.

Soln12

Suppose $x \in \cup \mathcal F$. Thus $x$ must exist in atleast one of the sets of $\mathcal F$. Suppose that $A_0 \in \mathcal F$ and $x \in A_0$. Since $\mathcal F \subseteq G$, then $A_0 \in G$. Thus x also exist in atleast one of the sets of $\mathcal G$. Or $x \in \cup \mathcal G$. Since $x$ is arbitrary, $\cup \mathcal F \subseteq \cup \mathcal G$.

Soln13

Suppose $x \in \cap \mathcal G$, then $x$ belongs to all the sets of $\mathcal G$. Since $\mathcal F \subseteq \mathcal G$, it follows that $x$ must belongs to all the sets of $\mathcal F$. Thus $x \in \cap \mathcal G \to x \in \cap \mathcal F$. Since $x$ is arbitrary, it follows that $\cap \mathcal G \subseteq \cap \mathcal F$.

Soln14

Suppose $x \in {\cup}_{i \in I} \mathcal P(A_i)$. Suppose $x$ exists in $\mathcal P(A_t)$ where $t \in I$. Thus $x \in \mathcal P(A_t)$. It follows that $x \subseteq A_t$. Now since $x \subseteq A_t$, it follows that $x \subseteq {\cup}_{i \in I} A_i$. Thus $x \in \mathcal P({\cup}_{i \in I} A_i)$. Or we can say that if $x \in {\cup}_{i \in I} \mathcal P(A_i)$ then $x \in \mathcal P({\cup}_{i \in I} A_i)$. Since $x$ is arbitrary, we can conclude that ${\cup}_{i \in I} \mathcal P(A_i) \subseteq \mathcal P({\cup}_{i \in I} A_i)$.

Soln15

Update: (04, Feb. 2019) Earlier solution was not correct, as pointed out in the comments section. Here is the updated version:

Suppose $\, X = {\cap}_{i \in I} \mathcal P(A_i) \,$. Or we can say that $\, X = \{ x \;\vert \; x \in {\cap}_{i \in I} \mathcal P(A_i) \} \,$. Since, for any $\, i \in I \,$, we have $\, x \in \mathcal P(A_i)\,$, it follows that $\, x \subseteq A_i \,$. Thus $\, X = \{ x \;\vert\; \forall{i \in I} (x \subseteq A_i) \} \,$ or, equivalently $\, X = \{ x \;\vert\; x \subseteq \cap_{i \in I} A_i\} \,$. Thus one possible value of $\, x = {\cap}_{i \in I} A_i \,$, such that $\, x \in X \,$. Thus $\, {\cap}_{i \in I} A_i \in {\cap}_{i \in I} \mathcal P(A_i) \,$.

Old version:

Suppose $x \in {\cap}_{i \in I} \mathcal P(A_i)$, then $\forall i \in I(x \in \mathcal P(A_i))$. Thus $x$ is a subset of all the sets of $A_i$ where $i \in I$. Or we can say that $x = {\cap}_{i \in I} A_i$. Thus ${\cap}_{i \in I} A_i = {\cap}_{i \in I} \mathcal P(A_i)$.

Soln16

Given that $\mathcal F \subseteq \mathcal P(B)$. Thus all the sets of A are subset of $B$. Suppose $x \in \cup \mathcal F$, then $x$ belongs to atleast one of the set of $\mathcal F$. Since all the sets of $\mathcal F$ are subsets of $B$, it follows that $x \in B$. Thus if $x \in \cup \mathcal F$, then $x \in B$. Since $x$ is arbitrary, it can be concluded that $\cup \mathcal F \subseteq B$.

Soln17

Suppose $x \in \cup \mathcal F$, then $x$ belongs to atleast one of the sets of $\mathcal F$. Since it is given that all the sets of $\mathcal F$ are subsets of every set of $\mathcal G$, it follows that $x$ exists in all the sets of $\mathcal G$. Or we can say that $x \in \cap \mathcal G$. Thus if $x \in \cup \mathcal F$, then $x \in \cap \mathcal G$. Since $x$ is arbitrary, we can conclude that $\cup \mathcal F \subseteq \cap \mathcal G$.

Soln18

(a)

It is given that $b = ma$ and $c = na$, where $m, n$ are integers. Adding the equations, we have $b + c = (m+n)a$. Since $m + n$ is also integer, it can be concluded that $a \vert (b+c)$.

(b)

Given that $bc = mac$. Since $c \neq 0$, it can be simplified to $b = ma$. Thus $a \vert b$.

Soln19

(a)

Suppose $z = \frac {y-x} 2$. Then $x + z = x + \frac {y-x} 2 = \frac {x + y} 2$. Similarly $y - z = y - \frac {y - x} 2 = \frac {x + y} 2$. Thus for $z = \frac {y-x} 2$, then $x + z = y - z = \frac {x+y} 2$. Since $z = \frac {y-x} 2$ is real, the equation is correct.

(b)

No, statement will not be correct as $z = \frac {y-x} 2$ is not an integer.

Soln20

The problem is negation of $\forall x (x^2 ≥ 0)$ is $% $. In the given proof, its negation is taken as $% $.

Soln21

(a) The issue with the proof is it started with $x \in A$ but in conclusion it is assumed that $x \in B$.

(b) $A = \{1,2\}$ , $B = \{0, 1, 2 \}$.

Soln22

The issue with the proof is that $y$ is fixed for the value of $x$. But for the goal of the theorem it should be arbitrary.

Soln23

(a)

It looks like theorem is correct except for only boundary case for empty set. If $A = \phi$ then $A \in \cup \mathcal F$ and $A \in \cup \mathcal G$. Thus for this case, we have no contradiction.

(b)

As seen above we can have only boundary case examples:

$\mathcal F = \{ \phi, \{1,2\}, \{3,5\} \}$
$\mathcal G = \{ \phi, \{4\}, \{8,9\} \}$

Thus $\mathcal F \cap \mathcal G = \{ \phi \}$, are not disjoint.

But $\cup \mathcal F \cap \cup \mathcal G = \phi$. Thus they are disjoint.

Soln24

(a)

Problem with the proof is $x$ and $y$ are considered equal, which may not be the case always.

(b)

Taking $x = 1$ and $y = 0$, the theorem is not correct.

Soln25

Let $x$ be an arbitrary real number. Let $y = 2x$. Now let $z$ be an arbitrary real number. Simplifying ${(x + z)}^2 − (x^2 + z^2)$
$\quad = x^2 + z^2 + 2xz - x^2 - z^2$
$\quad = 2xz$

Now taking $y = 2x$, we have $yz = 2xz$. Thus we can conclude that $yz = {(x + z)}^2 − (x^2 + z^2)$.

Soln26

(a)

• Goal: $\forall x P(x)$ and Given: $\exists x P(x)$:
For goal $\forall x P(x)$, we introduce an arbitrary variable $x$ and move forward.
For given $\exists x P(x)$, we introduce a new variable, say $x_0$ for which $P(x_0)$ is true and move forward for the proof.
Thus in both cases we move forward in the proof by introducing a variable.

• Goal: $\exists x P(x)$ and Given: $\forall x P(x)$:
For goal $\exists x P(x)$, we move forward by finding a value for which $P(x)$ is true.
For given $\forall x P(x)$, we move forward by finding a value that can help further in proof as $P(x)$ will be true for that value.
Thus in both cases we work on finding specific value to move forward with the proof.

(b) Not sure about the reason for these similarities.